Bisfenol em janelas críticas do desenvolvimento: efeitos do BPA e do BPS sobre perfil endócrino-metabólico em ratos Wistar - Silva, Beatriz Souza da (2019)
Bisphenol A (BPA) is an endocrine disruptor used in industrial applications, which has been detected in placenta and milk. Bisphenol S (BPS) is used as its main substitute and little is known about its effects during critical periods of ontogenetic development. To study the effects of BPA and BPS during gestation and breastfeeding on body composition, food intake, hormonal profile and behavior traits of young and/or adult Wistar rats. Mothers were divided into: Control, BPA10 or BPS10 (10μg/kg/day) and BPA50 or BPS50 (50μg/kg/day). Bisphenol was administered by gavage in the mothers from pregnancy until the end of lactation. Euthanasia occurred at weaning in postnatal day 21 (PN21) and 180 (PN180). In the BPA experiment, at weaning, BPA10 female offspring present high cholesterol and triacylglycerol, while BPA10 male offspring present lower plasma T3. BPA10 animals of both sexes have higher in progesterone, testosterone and estradiol. In adulthood, BPA10 and BPA50 females have a lower food consumption and higher insulinemia, while the BPA10 and BPA50 males have lower visceral fat, lower progesterone and lower testosterone levels. In addition BPA10 animals of both sexes have lower levels of T4 and only the males have lower estradiol levels. The BPA50 females present lower adipose mass, higher lean mass and lower corticosteronemia, while the BPA50 males show lower food intake. In the feeding study, BPA10 females and males ingest less hyperlipidic diet after 12 hours, while BPA10 males eat more hyperlipidic diet at 30 minutes. In the behavioral test, the BPA10 and 50 females present lower exploration, while the BPA10 group has hyperactivity. In the BPS experiment, at weaning, the BPS50 males offspring present hypotriglyceridemia and hyperthyroxinemia, while the females have higher at the levels of 25 (OH) D. BPS groups of both sexes have lower food intake. Males (BPS10 and 50) have lower visceral adiposity and BPS50 females have lower lipid accumulation in brown adipocytes. In behavioral test, BPS10 and 50 males have higher anxiety and locomotor activity, while the BPS10 females show less exploration. BPS10 and 50 males consume the hyperlipidic diet more in 30 minutes. The BPS10 females also consume more the hyperlipidic diet, but after 12 hours, this profile is inverted. In adulthood, BPS50 males show hypertriglyceridemia and reduction of T3 levels. The BPS10 females present lower progesterone, but BPS50 females present higher 25 (OH) D. In females of both groups, T4 is reduced. Maternal exposure of BPA or BPS during gestation and breastfeeding induces metabolic changes in the progeny throughout life, affects hormone levels and behavior. In addition, increased preference for a high-fat diet suggests a greater risk for obesity and its long-term consequences.